ANALISIS REKONSILIASI FISKAL ATAS LAPORAN KEUANGAN KOMERSIAL TERHADAP PAJAK PENGHASILAN BADAN TERUTANG PADA PT SATU CITA PROTENZA TAHUN 2014 - Edy Edy (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
A fiscal reconciliation of a commercial fi nancial statement against a company's corporate income tax needs to be done, which is important because field surveys indicate the occurrence of phenomena occurring in different reports. One of them is the fiscal financial statement of PT Satu Cita Protenza which there are costs that should be fiscal correction but not fiscal correction by PT Satu Cita Protenza. This led to errors in tax return reporting and income tax payable in 2014 PT Satu Cita Protenza. The purpose of this research is to find out (1) How is the implementation of Fiscal Reconciliation of Commercial Financial Statement as the basis for determining the amount of Income Tax of 2014 in PT Satu Cita Protenza (2) How to calculate Income Tax owed by Agency at PT Satu Cita Protenza 2014.Informants in this research are supervisor and tax staff member of PT Satu Cita Protenza. Data Collection Technique is done by open interview, Direct Observation and Written Documentation. Data Analysis Techniques that the authors use in this study is to use the method of deductive data analysis, unitizing and categorizing. Test Data Validity is done by Test Credibility, Transferbility Test, Depandability Test and Test Confirmability.The result of the research concludes that (1) The implementation of reconciliation conducted by PT Satu Cita Protenza is not in accordance with the applicable taxation provisions, it can be known from income tax, calculation of underpayment tax (PPh ps 29) Rp.13.625.361, -; (2) The implementation of the fiscal reconciliation calculation of the commercial report of PT Satu Cita Protenza from the financial accounting result conducted by PT Satu Cita Protenza based on SAK (Financial Accounting Standard), the company does not make fiscal correction in accordance with the principle of taxability deductibility, this is due to the difference in recognition of costs in fiscal reconciliation.